Minderheitenrecht in Ungarn in der Zwischenkriegszeit und dessen Anwendung im Alltag am Beispiel der Ungarndeutschen - Vitári, Zsolt (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
After 1920, a new stage began in terms of the endeavours for the ethnic homogenisation in Hungary. The most important obstacle of this was that in consequence of the delamination of the new frontiers of the country, the Germans, who formed a large ethnic minority were not able to find a way towards building their own groups and their self-organization. By means of the international organizations for the protection of minorities this would have been improved, but Hungary made efforts to prevent the German from finding their ethnic revival by bureaucratic means. The majority of these tools were the further developed versions of those employed before 1918. The powerful supervision, the inflaming popular feeling regarding the pan-German danger, prevention of their activity in the field of self-organization, the military enforcement of the law, operations of the police and gendarmerie, advertisements, arrests and violence formed a well-functioning system. Through this system, the international guaranteed rights of ethnic groups could ha